High-intensity interval training was more effective than moderate-intensity interval training in lowering creatine kinase and interleukin 6 levels among sports students - Nurpratiwi, Resti; Suyoko, Andri; Rusdiawan, Afif; Ciptorini, Ariesia Dewi; Sidik, Muhammad Asrul; Lestari, Bhekti; Samudra, Fajar Eka; Triardhana, Yanuar; Pranoto, Adi; Andriana, Laily Mita; Kusuma, I Dewa Made Aryananda Wijaya; Ismalasari, Rini (Physical Therapy Journal of Indonesia, 2025)
Background: This study aimed to prove that high-intensity interval training (HIIT) is superior to medium-intensity continuous training (MICT) in reducing creatine kinase and interleukin 6 (IL-6) levels in sports students after 4 weeks of exercise. Methods: The study examined the effects of two different training methods—MICT and HIIT. This study included 30 students aged 19-22 years, using a pretest-posttest control group design. Participants were randomly assigned to MICT, HIIT, or control groups (no training) and trained three times a week for four weeks. Creatine and IL-6 levels were analyzed by blood sampling. Data analysis included descriptive statistics, normality tests, and ANOVA tests to evaluate group differences. Results: HIIT was found to be more effective than MICT and the control group in reducing CK and IL-6 levels in sports students after 4 weeks of training (p< 0.001). Conclusion: The HIIT and MICT reduced creatine kinase and IL-6 levels compared to the control group, but HIIT was more effective in reducing creatine kinase and IL-6 levels than MICT in sports students after 4 weeks of exercise.